Literary references in women's narrative production for children (Journal of the College of Basic Education, 2026)
Children's stories, regardless of their origins, are based on several important references from the history of children's story writing; the most prominent of which are religious and literary heritage, folk tales, classical and translated world literature, as well as modern literature directed at children, both Arab and Western. All that we have mentioned constitutes a cultural and cognitive product that has influenced the output of women’s narrative writing at various and varying creative stages according to the answers provided in the questionnaires directed to female writers. This leads us to the following controversial question: Is all that we have mentioned included in the creativity of Iraqi female writers within the trend of writing for children?Although the writers were influenced by everything mentioned in their answers, and it was an advantage in refining their literary pens, the paradox when studying their narrative production was that each one was influenced by references that did not appear clearly in her writings. Not all of them wrote in the popular narrative heritage or wrote in the style of Arab experiences or in the style of translated classical literature, but rather this varied from one writer to another.